Management of tinea corporis, tinea cruris, and tinea pedis: A comprehensive review - Alok Kumar Sahoo; Rahul Mahajan (Wolters Kluwer Medknow Publications, 2016)
The prevalence of superficial mycotic infection worldwide is 20-25% of which dermatophytes are the most common agents. Recent developments in understanding the pathophysiology of dermatophytosis have confirmed the central role of cell-mediated immunity in countering these infections. Hence, a lack of delayed hypersensitivity reaction in presence of a positive immediate hypersensitivity (IH) response to trichophytin antigen points toward the chronicity of disease. Diagnosis, though essentially clinical should be confirmed by laboratory-based investigations. Several new techniques such as polymerase chain reaction (PCR) and mass spectroscopy can help to identify the different dermatophyte strains. Management involves the use of topical antifungals in limited disease, and oral therapy is usually reserved for more extensive cases. The last few years have seen a significant rise in the incidence of chronic dermatophyte infections of skin which have proven difficult to treat. However, due to the lack of updated national or international guidelines on the management of tinea corporis, cruris, and pedis, treatment with systemic antifungals is often empirical. The present review aims to revisit this important topic and will detail the recent advances in the pathophysiology and management of tinea corporis, tinea cruris, and tinea pedia while highlighting the lack of clarity of certain management issues.